Analisis genetik molekul dan imunofenotip penyakit non-Hodgkin's lymphoma di Kelantan - Khairani Idah , Mokhtar (2001)
Non-Hodgkin's lymphoma (NHL) is a heterogeneous malignancy. Recent advancement in techniques in the field of immunology and molecular biology enables the diagnosis and classifications of NHL to be made satisfactorily. Protein expression criteria such as p53 and bcl-2 play an important role in classifying lymphoma. There are three main objectives in this study. First, to observe the effectiveness of flow cytometry analysis as a technique for lineage assignment in NHL using fresh single cell suspension samples. Second, to detect immunoglobulin heavy (lgH) chain gene rearrangement as a technique to identify monoclonal population in NHL cases by polymerase chain reaction (PCR). Third, to detect the expression and distribution of p53 and bcl-2 protein on different grades of NHL by immunohistochemistry technique. Lymph node samples were obtained from patients suspected of having lymphoma. In flow cytometry analysis, single cell suspension were prepared from 37 lymph node samples, reacted with monoclonal antibodies and analysed using FACScan machine. Detection of IgH gene rearrangement was done using DNA extracted from 43 fresh or frozen lymph nodes and was subjected to PCR using VpJJH specific primer. Monoclonal population was represented by amplified band at 90-160bp. Immunohistochemistry staining was done using monoclonal antibodies p53 (00-7) and bcl-2 (clone 124) on 56 paraffin embedded tissue sections. Flow cytometry analysis had .correctly assigned the lineage in 11/14 cases of confirmed NHL-B and 1 case of NHL-T. By doing peR in detecting IgH gene rearrangement, monoclonal population was observed in 18/21 cases of B lineage NHL, 2 cases of NHL-T and 2 cases of Hodgkin's disease while none was observed in reactive, metastatic carcinoma and tuberculosis. P53 and bcl-2 protein expression was analysed in NHL from different grades. Positive p53 pr<?tein expression was observed more frequently in cases of NHL from intermediate and high grade while bcl-2 protein expression was observed frequently in intermediate grade NHL especially in diffuse large cell subtypes. In conclusion, by flow cytometry analysis, lineage assignment coutd be assigned confidently on cases of B-NHL expressing abnormal kappa:lambda ratio and positive expression of B-cell surface markers. IgH gene rearrangement analysis could be used to show monoclonal population in cases of B lineage NHL. Thus, flow cytometry and detection of IgH gene rearrangement could be an adjunct to immunohistopathology in . making diagnosis and assigning lineage in NHL. Immunohistochemistry analysis could detect the expression of p53 and bcl-2 protein in NHL. Frequent expression of p53 observed in intermediate/high grade NHL and bcl-2 in intermediate grade could be used to show levels of aggressiveness in this malignancy.